Analisis Rasio Likuiditas, Rasio Aktivitas dan Rasio Profitabilitas untuk Menilai Kinerja Keuangan pada PT Astra Otopartstbk Periode (2008-2017) - Khair, Oki Iqbal (Universitas Pamulang, 2020)
The purpose of this study is to assess the company's financial performance at PT Astra Otoparts Tbk during the period 2008-2017. This research is quantitative descriptive research in the form of financial statements. The financial statements are data obtained from PT Astra Otoparts Tbk, while the analytical tool used is financial ratio analysis which includes liquidity, activity and profitability. The results of the liquidity ratio are based on the average CR and QR calculation in the last ten years at 1.64 and 1.08, from the two indicators it can be concluded that the financial performance of PT Astra Otoparts Tbk is in the